From research to publication: a must-have handbook for novice quantitative researchers - Husin, Nor Azilah; Saad, Mazni; Yulia, Astri (IIUM Press, 2025)
This book provides a step-by-step guide, cautions, and tips from the start of the research process until the study findings are made public, and as such, this book stands out among other research books in the market. This book is divided into two sections. Five chapters make up the first section, which helps novice researchers get acquainted and involved in the entire process of performing and writing research. The second section discusses the publication of the study’s findings. To help our researchers’ work be publishable, the final three chapters in the second section are provided. Anyone directly involved in research will find this book helpful. It is suitable for use as teaching and learning material for courses related to research methodology at the undergraduate and graduate levels. Examples are provided at the end of each section to help readers better understand the topics covered. This book helps researchers, especially novice and young researchers, develop initial ideas about how to write for a journal and get it published in a suitable journal. In this era of globalisation and lifelong learning, it is hoped readers of all levels can fully benefit from this book and realise their goals and aspirations through research work and personal development.